2006
DOI: 10.1021/om0508334
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Weakly Coordinating Anions. Mono- and Polynuclear Halo(perfluoroaryl)metalates as Cocatalysts for Stereospecific Olefin Polymerization:  Synthesis, Structure, and Reactivity

Abstract: A series of mononuclear and polynuclear trityl (perfluoroaryl)borate, -aluminate, and -gallate reagents, potential cocatalysts/activators for metallocene-mediated olefin polymerization, have been synthesized via fluoride abstraction from trityl fluoride (Ph3CF) by the organo Lewis acid reagents B(C6F5)3 (1), B(o-C6F5C6F4)3 (2), and Al(C6F5)3 (3), by derivatization of Ph3C+FAl(o-C6F5C6F4)3 - (4), and by reaction of trityl fluoride with in situ generated Ga(C6F5)3 (5). Reaction of trityl fluoride with the tris(p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 46 publications
5
43
0
Order By: Relevance
“…[144][145][146] Ac lear difference between bridged WCAsf eaturing Lewis acids based on aluminum and boron is that aluminum forms the most stable bridged anion with the hard fluoride ligand bridging,w hereas the softer cyanide ligand has been used for the formation of an umber of bridged WCAsb ased upon the B(C 6 F 5 ) 3 Lewis acid. [155,156] [147,148] In an elegant extension, as eries of very large WCAs based upon the general motif [E{CNB(C 6 F 5 ) 3 } n ] À (where E = N, C, or Ba nd n = 2, 3, or 4) have been reported as anumber of synthetically useful salts and their formation also investigated by computational methods.…”
Section: Bridged Wcasmentioning
confidence: 99%
See 2 more Smart Citations
“…[144][145][146] Ac lear difference between bridged WCAsf eaturing Lewis acids based on aluminum and boron is that aluminum forms the most stable bridged anion with the hard fluoride ligand bridging,w hereas the softer cyanide ligand has been used for the formation of an umber of bridged WCAsb ased upon the B(C 6 F 5 ) 3 Lewis acid. [155,156] [147,148] In an elegant extension, as eries of very large WCAs based upon the general motif [E{CNB(C 6 F 5 ) 3 } n ] À (where E = N, C, or Ba nd n = 2, 3, or 4) have been reported as anumber of synthetically useful salts and their formation also investigated by computational methods.…”
Section: Bridged Wcasmentioning
confidence: 99%
“…[144,155] Ty pical examples include [( F RO) 3 Al-X-Al-(OR F ) 3 ) 2 ] À X = F, [142] Cl, [145] X = OH; [146] [155] and [Ph 3 [155] Fort he Synthesis of Reactive Cations:W ei nclude some recent and exemplary examples highlighting this approach for the formation of reactive cations.S imple halide abstraction from the ruthenium fluoride complexes [Ru(L) 2 (CO) 2 F 2 ] (where L = PPh 3 or NHC) by the Lewis acids BF 3 ,P F 5 ,a nd B(C 6 F 5 ) 3 gives the corresponding fluoride-containing WCAs. Moreover,t his approach is ideally suited to the formation of bridged WCAso ft he type [LA-X-LA] À ,a nd even higher aggregates of bridging species of the type [LA-X-LA-X-LA] À can be formed.…”
Section: Strong Lewis Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies has focused on improving these coactivators; good results have been reported for methylalumoxane (MAO), 32 perfluoroarylboranes, 33,34 perfluoroarylborates and aluminates, 35,36 or mixtures of alkylaluminum and perfluoroarylborane and borates. [37][38][39] Alkoxides have been considered as alternatives for Cp ligands. The titanium complexes based on these ligands, and among them, those with the general formula Ti(OR) 2 Cl 2 or Ti(OR) 4 have been known for a while and are used as Lewis acid catalysts or at stoichiometric amounts for a wide scope of organic reactions such as hetero-Diels-Alder reactions, Michael additions, and others.…”
Section: Introductionmentioning
confidence: 99%
“…For early transition complexes, the metals generally belong to groups 3 or 4. High activities in the polymerization process can be achieved with the use of co-catalysts such as methylalumoxane (MAO) [5], perfluoroarylboranes [6][7][8], perfluoroarylborates and aluminates [9,10], or mixtures of alkyl aluminum and perfluoroaryl borane and borate [11][12][13]. The polymers obtained by these systems are generally highly stereoregular and display narrow polydispersities.…”
Section: Introductionmentioning
confidence: 99%